Role of Nintedanib in COVID-19-Related Lung Fibrosis - Alif Fathurrachman; Linda Andriani; Rouly Pasaribu; Sudarto Sudarto; Ahmad Rasyid; Zen Ahmad; Tommy Setiawan (Jurnal Respirasi, 2022)
In December 2020, Indonesia was introduced to the long Coronavirus disease 2019 (COVID-19) phenomenon. The Centers for Disease Control and Prevention (CDC) introduced the term "post-COVID condition" as a health problem that persists after four weeks from the first exposure to COVID-19. The National Institute for Healthcare and Care Excellence (NICE) classifies COVID-19 infections into three categories based on disease duration: (1) acute infection for up to 4 weeks; (2) ongoing infection within 4-12 weeks; and (3) post-COVID-19 syndrome for more than 12 weeks and not associated with an alternative diagnosis. One of these phenomena is lung fibrosis. About 80% of COVID-19 survivors had mild to severe chest X-rays in 6 months of follow-up with decreasing lung function. COVID-19-related lung fibrosis is still not widely researched. COVID-19 survivors who develop lung fibrosis usually recover independently, but some develop persistent lung fibrosis. The use of antifibrotic agents, such as nintedanib, has long been approved for idiopathic pulmonary fibrosis (IPF). However, its use in the cases of lung fibrosis due to COVID-19 has not been widely studied.  Nintedanib is a tyrosine kinase inhibitor. It inhibits receptor activity of vascular endothelial growth factor (VEGF), platelet-derived growth factor (PDGF), and fibroblast growth factor (FGF). Those actions will eventually inhibit the proliferation, migration, and transformation of fibroblasts into myofibroblasts in lung fibrogenesis. Therefore, an antifibrotic agent is potentially needed to inhibit COVID-19-related lung fibrosis to improve quality of life and prevent further lung damage.